2022
DOI: 10.3389/fphys.2022.936750
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Related Factors of White Coat Hypertension and Masked Hypertension in Shunde District, Southern China

Abstract: Background: White coat hypertension (WCH) and masked hypertension (MH) can increase the risk of target organ damage. Home blood pressure monitoring is an important method for detecting WCH and MH. However, the prevalence and related factors of WCH and MH in China have been rarely reported.Objective: To explore the prevalence and related factors associated with white coat hypertension (WCH) and masked hypertension (MH) in Shunde District, Southern China.Methods: This study recruited subjects from the Physical E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The reported prevalence of WCHTN differs according to the criteria for diagnosing this type of HTN. For instance, Zhu et al reported a WCHTN in 5.1% of the Chinese population [ 127 ]. In a study, using the criteria of daytime, 24-h, or all ambulatory periods, the prevalence of WCHTN in the untreated group was found to be 41.3%, 35.2%, and 26.1%, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…The reported prevalence of WCHTN differs according to the criteria for diagnosing this type of HTN. For instance, Zhu et al reported a WCHTN in 5.1% of the Chinese population [ 127 ]. In a study, using the criteria of daytime, 24-h, or all ambulatory periods, the prevalence of WCHTN in the untreated group was found to be 41.3%, 35.2%, and 26.1%, respectively.…”
Section: Reviewmentioning
confidence: 99%